Averting comfortable lifestyle crises. (1st December 2013) - Bilton, Rod
How have climate change and diet shaped the evolution of human energy metabolism, and responses to vitamin C, fructose and uric acid? Through the last three millennia observant physicians have noted the association of inappropriate diets with increased incidence of obesity, heart disease, diabetes and cancer, and over the past 300 years doctors in the UK observed that overeating increased the incidence of these diseases. Anthropological studies of the Inuit culture in the mid-nineteenth century revealed that humans can survive and thrive in the virtual absence of dietary carbohydrate. In the 1960s, Cahill revealed the flexibility of human metabolism in response to partial and total starvation and demonstrated that type 2 diabetics were better adapted than healthy subjects to conserving protein during fasting. The potential role for brown adipose tissue thermogenesis in temperature maintenance and dietary calorie control was suggested by Rothwell and Stock from their experiments with 'cafeteria fed rats' in the 1980s. Recent advances in gene array studies and PET scanning support a role for this process in humans. The industrialisation of food processing in the twentieth century has led to increases in palatability and digestibility with a parallel loss of quality leading to overconsumption and the current obesity epidemic. The switch from animal to vegetable fats at the beginning of the twentieth century, followed by the rapid increase in sugar and fructose consumption from 1979 is mirrored by a steep increase in obesity in the 1980s, in the UK and USA. Containment of the obesity epidemic is compounded by the addictive properties of sugar which involve the same dopamine receptors in the pleasure centres of the brain as for cocaine, nicotine and alcohol. Of the many other toxic effects of excessive sugar consumption, immunocompromisation, kidney damage, atherosclerosis, oxidative stress and cancer are highlighted. The WHO and guidelines on sugar consumption include: alternative non-sugar sweeteners; toxic side-effects of aspartame. Stevia and xylitol as healthy sugar replacements; the role of food processing in dietary health; and beneficial effects of resistant starch in natural and processed foods. The rise of maize and soya-based vegetable oils have led to omega-6 fat overload and imbalance in the dietary ratio of omega-3 to omega-6 fats. This has led to toxicity studies with industrial trans fats; investigations on health risks associated with stress and comfort eating; and abdominal obesity. Other factors to consider are: diet, cholesterol and oxidative stress, as well as the new approaches to the chronology of eating and the health benefits of intermittent fasting.